Lexical richness of pre-sessional and advanced EFL learner: A comparison - Engku Ibrahim, Engku Haliza; Muhamad, Ainon Jariah; Esa, Zaleha (2016)
One of the challenges of an EFL learner is to increase the vocabulary size and to increase their vocabulary richness. This study reports on the lexical richness of 139 pre-sessional students and 140 advanced level students studying at an English medium university. Pre sessional student are students who are about to enrol in their faculties while the advanced students are students who about to graduate. Both groups have met the minimum entry requirement of the university which is an equivalent of IELTS band 6 or TOEFL 550. The students in this study attended intensive English courses at the pre-sessional level. Once they are accepted into their faculties, it is assumed that they will maintain progress of their English language proficiency generally and their vocabulary size specifically, on their own. The specific objectives of this study are (1) to determine the difference between the type-token ratio in the pre-sessional students’ essays and that of the advanced level students’ essays; (2) to determine the difference between the use of 2000-word level in the pre-sessional students’ essays and that of the advanced level students’ essays; and to determine the difference between the use of academic words in the pre-sessional students’ essays and that of the advanced level students’ essays. Students’ lexical richness vocabulary were measured using RANGE program developed by Nation, Heatley & Coxhead (2002). Although this study is still in progress, it is predicted that advanced learner students would be using a greater frequency of words at the upper levels of 5,000 and 10,000 word levels implying that there is a development of higher frequency vocabulary in advanced learners thus indicating greater lexical richness.